2019
DOI: 10.3390/met9030338
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Heat Treatment Parameters on the Cracks Growth under Cyclic Bending in St-Ti Clad Obtained by Explosive Welding

Abstract: The current work focuses on the effect of time and temperature of annealing on the change in the structure and cracks growth and fatigue life of the steel-titanium bimetal obtained by explosive welding. Cyclic bending tests were performed for different levels of annealing temperature on bimetal specimens of a rectangular cross-section. The fatigue crack growth was measured by microscopy. Structure changes of steel, titanium and bond area resulted in a different micro-hardness distribution. The relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…In these studies, the bond interface Steel/Ti was parallel to a neutral plane of bending, and the interface was located a few millimetres away from the specimen surface where the highest stress was generated, implying that, although the multilayer composite carries the cyclic loading, the bond interface is less deformed and stressed than the specimen surface of the homogenous material. Thus, the cracks preferably initiate on the specimen surface, with subsequent propagation into the material through the bond interface, and that is confirmed by observations reported in [29][30][31]. The crack propagation behaviour into the interface could be modified owing to the mismatch of the material layers properties [32,33].…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…In these studies, the bond interface Steel/Ti was parallel to a neutral plane of bending, and the interface was located a few millimetres away from the specimen surface where the highest stress was generated, implying that, although the multilayer composite carries the cyclic loading, the bond interface is less deformed and stressed than the specimen surface of the homogenous material. Thus, the cracks preferably initiate on the specimen surface, with subsequent propagation into the material through the bond interface, and that is confirmed by observations reported in [29][30][31]. The crack propagation behaviour into the interface could be modified owing to the mismatch of the material layers properties [32,33].…”
Section: Introductionsupporting
confidence: 77%
“…Despite the detection of traits for the fatigue crack initiation in explosively welded metallic composites, only few studies concerning this problem can be found in the literature. Some of them analysed the effect of the heat treatment on the fatigue life of bimetallic plates subjected to cyclic bending [28][29][30]. In these studies, the bond interface Steel/Ti was parallel to a neutral plane of bending, and the interface was located a few millimetres away from the specimen surface where the highest stress was generated, implying that, although the multilayer composite carries the cyclic loading, the bond interface is less deformed and stressed than the specimen surface of the homogenous material.…”
Section: Introductionmentioning
confidence: 99%
“…Modern techniques such as explosive cladding and microwave cladding are being used in several manufacturing units. In explosive weld zones, fatigue life varies with temperature of exposure and time of exposure, resulting in grain growth and recrystallization in the sample as well as decarburization occurring at the interface zone [30]. Microwave cladding is one of the most economical and proficient ways of cladding where uniform surface texture and properties can be obtained with uniform heat distribution throughout the clad, with good tribological properties [31].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their high values of hardness and brittleness, such IMPh formation leads to hot cracking, which promotes intensive destruction of bimetal plate welded joints [1,6]. Even overheating above 500 °C, owing to structural transformations, can have a negative impact on the mechanical properties of steel-titanium plate joints; in particular, it can lower the fatigue life [7]. In addition to crack formation during welding, there is the risk of fatigue crack initiation during further service of steel-titanium joints [8] It is known that titanium can easily interact with iron to form highly brittle intermetallic compounds, due to considerable differences in their physical-mechanical properties [9,10].…”
Section: Introductionmentioning
confidence: 99%